Influence of particle modulus (softness) and matrix rheology on the sensory experience of 'grittiness' and 'smoothness'. (June 2020) - Shewan, Heather M.; Stokes, Jason R.; Smyth, Heather E.
Abstract: The perception of particles that arises during food oral processing, described using sensory terms such as gritty, powdery, chalky and rough, is critical to sensory perception and consumer satisfaction. Here, a relationship between particle modulus (softness), particle concentration, matrix phase viscosity and sensory experience of grittiness and smoothness is elucidated using well-defined model systems. The systems consist of a model set of fifteen suspensions of micro-hydrogel agar spheres of around 100 μm in size that vary in modulus and are dispersed in aqueous mediums with varying rheological properties. A key finding is that, for suspensions with the same particle concentration and matrix phase viscosity, increasing particle modulus across the range of 100–600 kPa, causes an increase in in-mouth detectability along with an increase in sensory perception of particles, termed size of particles and a decrease in smoothness perception. It is also found that particle concentration (10–80 w/w %) and matrix phase rheology have little influence on particle detectability for both the lowest and highest modulus particles. The results provide support to the notion that for heterogeneous food and beverages samples, micromechanical properties (i.e. level of the individual constituents) play a key role in their perceived texture and mouthfeel in conjunction with bulk properties such as rheology. The insights from this can be used in understanding how heterogeneity, which includes that arising from particle addition or as a by-product of the manufacturing process, may be considered in the rational design and development of products without compromising consumer acceptance. Graphical abstract: Image 1 Highlights: Increasing microgel modulus increases sensory 'particle size' and 'detectability'. Decreasing microgel modulus increases sensory 'smoothness'. Particle modulus has greater influence on particle detectability than matrix phase rheology.